Tinkering through transition: on 'doctoring' as an early-career academic in physical education and sport pedagogy. Issue 1 (2nd January 2017) - Williams, Benjamin; Christensen, Erin; Occhino, Joseph
Abstract : This article addresses the notion of 'making it' as an early-career academic in physical education and sport pedagogy. In it, we draw on the tradition of material semiotics to reflect on our shared journeys from doctoral student to beginning scholar and beyond. By attuning ourselves to the relationality, materiality and precariousness of our experiences, we offer an answer to the question of what it takes to 'make it' as an early-career academic by advocating the practice of 'making do' or 'doctoring.' We develop this argument, first, by describing the narrative methods we used to conduct our inquiry and by explaining the material-semiotic ideas we used to explore the stories it generated. Then, we tell tales of our transitions from higher degree research student to early-career academic, focusing specifically on our ongoing, collective efforts to make do. In our discussion, we explore these narratives and attend to three features of our actions and activities as early-career academics; namely semiotic relationality, material heterogeneity and the precarious processes of heterogeneous engineering through which we sought to make a career in our field. We conclude by encouraging beginning scholars in physical education and sport pedagogy to become sensitive to these aspects of their own agency, and to experiment, experience and tinker together in ways that are attentive, inventive, caring and persistent.